Embedded, Laminated and Mounted Specimens of Plants and Animals - Giri, Bindu (SCHOOL SCIENCE, 2017)
I am a science teacher. While conducting experiments with my students in the lab, one of the specimens fell down from the student‘s hands and broke. So I enquired about the price and found it very costly. I found some interesting methods to preserve the plants and animals by putting my innovation. Embedded specimen is the replacement of traditional dry and soak specimen because of its advantages: no poison, no smell, easy to transport, not easily broken, can be preserved forever. This is unique real acrylic resin insects or the laminated. It can be an educational specimen for school, museum, and home. The outside material is safe for human. A herbarium specimen is a pressed plant sample deposited for future reference. It supports research work and may be examined to verify the identity of the specific plant used in a study. Specimens are pressed by placing the specimen between the papers under the weight. The objective of pressing plants is to extract moisture in the shortest period of time. My process was laminating herbarium specimen and dried insects ironing the lamination papers by ordinary iron box adjusting the temperature. We have many plants and animals which are explained in the textbooks from Classes V to X. I had collected many of the plants and insects which were available and tried to laminate, embed and mount.